2021
DOI: 10.1016/j.vaccine.2021.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in coverage of COVID-19 vaccination: A population register based cross-sectional study in Wales, UK

Abstract: The COVID-19 pandemic has highlighted existing health inequalities for ethnic minority groups and those living in more socioeconomically deprived areas in the UK. With higher levels of severe outcomes in these groups, equitable vaccination coverage should be prioritised. The aim of this study was to identify inequalities in coverage of COVID-19 vaccination in Wales, UK and to highlight areas which may benefit from routine enhanced surveillance and targeted interventions. Records within the Wales Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 23 publications
(26 reference statements)
5
80
1
Order By: Relevance
“…Less deprived, mainly urban areas achieved higher coverage so, by the end of the third wave, protection was strongly socially patterned. This is consistent with experience elsewhere, in the UK and the United States [ 12 , 13 , 44 , 45 ]. As expected, coverage was especially low in areas with the highest proportion of Roma population, even more so than in the other most deprived areas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Less deprived, mainly urban areas achieved higher coverage so, by the end of the third wave, protection was strongly socially patterned. This is consistent with experience elsewhere, in the UK and the United States [ 12 , 13 , 44 , 45 ]. As expected, coverage was especially low in areas with the highest proportion of Roma population, even more so than in the other most deprived areas.…”
Section: Discussionsupporting
confidence: 92%
“…Those taking this perspective argue that relying on vaccines is less likely to exacerbate inequalities. However, inequities in the uptake of COVID-19 vaccination, which are reported from several countries, may jeopardize this goal [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elliott and colleagues found a lower intent to get vaccinated in black than white and Asians, in essential workers, and the most vulnerable groups of the population [ 18 ]. A study conducted in Wales, UK, using administrative data, with a methodology similar to this study, found that in April 2021, subjects living in a more deprived area or belonging to an ethnic group other than white were less likely to be vaccinated [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Median (IQR) of RBD-specific memory B cell spots at day 0 was 2 (0-10), increased to 18 (14-36) at day 28, and declined to 6 (4-20) SFU/10 6 PBMCs at day 90. Compared with IM study of 4 (0-16) at day 0, 26 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) at day 28, and 8 (4-16) SFU/10 6 PBMCs at day 90.…”
Section: T and B Cell Responses Evaluated By Elispot Assaymentioning
confidence: 88%
“…As current situation of COVID-19 pandemic, more vaccine supply is still needed for many countries as vaccine coverage is not enough to prevent mortality [31][32][33]. Almost half of the world population has received at least one dose of COVID-19 vaccine but only 2.2% of people in low-income countries have received vaccine [34].…”
Section: Discussionmentioning
confidence: 99%